Gramaticalització i adquisició de llengües: l'adquisició de la morfologia de passat en aprenents de català com a segona llengua - Comajoan Colomé, Llorenç; Pérez Saldanya, Manuel (Caplletra. Revista Internacional de Filologia, 2003)
This article applies grammaticalization theory to the process of acquisition of past morphology (perfective and imperfective) by learners of Catalan as a foreign language. It argues that diachronic and acquisitional grammaticalization show clear parallels in the evolution of past morphology. These parallels are contrasted with the aspect and discourse hypotheses, which argue that lexical and discourse characteristics of verbal predicates can explain the development of past morphology in a second language. Beginner data on the acquisition of Catalan confirmed that both lexical aspect and discourse grounding contribute to the grammaticalization of past meaning in interlanguage.